Impact of income diversification on the business performance of Vietnamese commercial banks - Duong Thuy Phan; Trong Tai Nguyen; Thi Thanh Hoang (Cogent Business & Management, 2022)
The article evaluates the impact of income diversification on business performance of Vietnamese commercial banks in the period 2010-2020. The study collected data from from the financial statements of 29 commercial banks listed on both the Ho Chi Minh stock exchange and the Hanoi stock exchange in the period 2010-2020 from the FiinPro Database. GMM regression method is used to analyze the impact of income diversification on the business performance of Vietnamese commercial banks. The analysis results show that the business performance of commercial banks is influenced by many factors, the most influential factors are income diversification, the scale of credit activities, and the efficiency of management physical. Based on empirical results, the study proposes some recommendations to help banks improve businessperformance.
Keywords: 650; income; commercial banks; business performance